MODERN ASPECTS AND METHODS OF FORMING MUSIC LITERACY IN PRIMARY GRADE STUDENTS - Sadinova Aziza Nizom qizi (The Conference Hub, 2025)
Currently, the implementation of textbooks, study guides, as well as methodologies based on advanced scientific and methodological aspects that ensure the educational process in all forms of educational institutions of the continuous education system, using the achievements of science and technology, advanced technology, and scientifically ensuring the goals, content, methodological tools and organization of education for the younger generation is one of the urgent problems of musicology. As a producer of educational services, the individual participates in the educational process in the knowledge and science, culture and services.
Keywords: primary school students, musical literacy, modern aspects, methods, etc.